Anodic films on single phase Ni-Mo alloys in acid solution - Mitrovic-Scepanovic, Vesna (My University, 1982)
The anodic oxide films of single phase Ni-Mo alloys (5-15 wt % Mo) formed in 0.15 N Na₂SO₄ (pH 2.8) have been investigated using electrochemical techniques, atomic absorption spectroscopy, Auger electron spectroscopy and X-ray photoelectron spectroscopy. The anodic oxide film of Ni formed under the same condition has been used as a reference in order to study the effect of molybdenum addition on the nature of the passive film of nickel. The electrochemical studies have indicated a negative effect of molybdenum addition to stability of the passive film and a different mechanism of the film growth on the alloys with respect to that on nickel. Dissolution of nickel and molybdenum during the film formation has been found to proceed in proportions other than their ratio in the alloy and which was also time dependent. Selective dissolution of molybdenum has been found during the initial stages of anodization and its enrichment in the film at longer anodization times. Chronoamperometric measurements combined with dissolution analysis suggested an increase of the film thickness with anodization time. Auger electron spectroscopy with ion sputtering confirmed the anodization time dependence of the film thickness and an enrichment of the film-solution interface in molybdenum. The thickness of the passive film of nickel has not been found to change significantly with adonization time. Characterization of nickel and molybdenum species in the film has been based on the findings of x-ray photoelectron spectroscopy, which combined with the evidence offered by structure analysis (RHEED), suggested the passive film to be a two-phase oxide film containing defective or hydrated NiO and probably amorphous MoO₃. A model which explains the growth of two-phase oxide coverage on Ni-Mo alloys has been proposed.
Keywords: Materials Science and Engineering; Metallurgy; Materials Science and Engineering